The Legal Standing and the Professional Liability of the Project manager in the Context of his Contemporary Responsibilities - Masadeh, Mohammad Saleh (2016)
This dissertation reviews the legal standing and the professional liability of the contemporary project management practice where construction specialists and professionals such as cost managers, building surveyors, commercial managers, architects and engineers have merged into the realm of project management area of expertise. As a result, the project management consultancies have expanded their services beyond their well know classical role where it is of norm nowadays to see the project manager performing the role of the contract administrator, acting as an employer’s agent from one side, and as a certifier from the other side. Consequently, the role of the engineer under FIDIC forms of contracts – the most used in the Middle East and the Gulf Countries - and particularly under FIDIC Red Book 1999, has been affected where his role has been practically restricted to the design & technical supervision role only, shifting the responsibility of administering the main works contract and certifying the works to the project manager. Having in mind this exponential increase in the project manager’s responsibilities, it is imperative to understand what his legal position is under the UAE law in view of his duties and responsibilities where this dissertation endeavored to present a simple legal analysis, highlighting the project manager’s professional liabilities, and documenting a list of recommendations which helps in defining the project manager within a recognized legal and administrative framework.